Combined Transcriptome and Proteome Analysis of Anthers of AL-type Cytoplasmic Male Sterile Line and Its Maintainer Line Reveals New Insights into Mechanism of Male Sterility in Common Wheat - Hao, Miaomiao; Yang, Wenlong; Li, Tingdong; Shoaib, Muhammad; Sun, Jiazhu; Liu, Dongcheng; Li, Xin; Nie, Yingbin; Tian, Xiaoming; Zhang, Aimin (Frontiers in Genetics, 2021)
Cytoplasmic male sterility (CMS) plays an essential role in hybrid seeds production. In wheat, orf279 was reported as a CMS gene of AL-type male sterile line (AL18A), but its sterility mechanism is still unclear. Therefore, transcriptomic and proteomic analyses of the anthers of AL18A and its maintainer line (AL18B) were performed to interpret the sterility mechanism. Results showed that the electron transport chain and ROS scavenging enzyme expression levels changed in the early stages of the anther development. Biological processes, i.e., fatty acid synthesis, lipid transport, and polysaccharide metabolism, were abnormal, resulting in pollen abortion in AL18A. In addition, we identified several critical regulatory genes related to anther development through combined analysis of transcriptome and proteome. Most of the genes were enzymes or transcription factors, and 63 were partially homologous to the reported genic male sterile (GMS) genes. This study provides a new perspective of the sterility mechanism of AL18A and lays a foundation to study the functional genes of anther development.